Communication strategy of public relation in building competiveness of higher education quality: A case of stain Tengku Dirundeng Meulaboh - Mukhsinuddin Mukhsinuddin (Proceedings of AICS - Social Sciences, 2017)
The basic purpose of understanding the Strategy is planning and management to accomplish a goal,